Penjara sebagai Lembaga Pendisiplinan: Sejarah Kehidupan Sehari-Hari di Penjara Perempuan Malang, 1984-2004 - Muhtarom, Ian Iradatillah; Subekti, Arif (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2025)
This research aims to examine the history everyday of life in Malang Women's Prison in the period 1984-2004 using historical methods, focusing on the continuity that occurred in daily life in prison after the correctional concept was implemented in 1964. The research focused on two daily routines in Malang Women's Prison: meals and skills training. The History of Everyday Life approach in this research is used to reconstruct the history of prison as a disciplinary institution using the perspective of everyday life. The conclusions of this research are; first, Malang Women's Prison was built as a marker of infrastructure progress and a symbol of stability of the urban environment, because of the prison's function as a place to discipline urban society; second, the State intervenes in all aspects of the daily life of prisoners through regulations applied in Malang Women's Prison; third, discipline is a discourse developed by Foucault as a genealogy of power in the early 19th century where routines as part of daily life, are part of discipline, with the aim of creating obedient bodies through power control.